PRODUCTION OF CHARCOAL BRIQUETTE FROM RICE HUSK AS AN ALTERNATIVE SOLUTION FOR PROCESSING AGRICULTURAL WASTE IN KULO DISTRICT: PEMBUATAN BRIKET ARANG DARI SEKAM PADI SEBAGAI SOLUSI ALTERNATIF PENGOLAHAN LIMBAH PERTANIAN DI KECAMATAN KULO - Nurul Qisti; Deril Alfiance Kaligi (PT. ROCE WISDOM ACEH, 2025)
Sidenreng Rappang Regency is one of the largest rice-producing regencies in South Sulawesi. One of the wastes produced in rice production is rice husks. Rice husks in Sidenreng Rappang Regency have not been optimally used to create useful and economically valuable products. One alternative solution to utilize this rice husk waste is to make Charcoal Briquettes as an environmentally friendly alternative fuel product. This activity was carried out in Madenra Village where the main target was the Madenra Village Farmer Group in the form of Socialization Activities for Making Rice Husk Charcoal Briquettes and Direct Training by Agricultural Product Technology students under the guidance of lecturers. This Community Service aims to provide the community with information about alternative solutions for utilizing rice husk waste, applying it, and developing the product as a product with economic value. This can help the economy of the community itself.